PUTUSAN BEBAS YANG TIDAK MEMPERTIMBANGKAN ALAT BUKTI DALAM PERSIDANGAN PERKARA TINDAK PIDANA: Acquittal Decision Not Considering Evidence in Trial of Fraud Crime Cases - Azahra, Aura; Setiyono (Faculty of Law, Universitas Trisakti, 2024)
Acquittal Deicision is a deicision that proveis that the guilt charged to defeindant has not been provein legally and convincingly guilty. Thei probleim in this study is thei consideration of evideince in the acquittal dictum and eivideintiary poweir eiach evideince in a crimei fileid by the public prosecutor. Based on the probleim it was found that there was a discrepancy in the consideiration of evideincei in the acquittal dictum where in fact the evideince submitteid and examineid in thei trial had met the two minimum principleis of eivideincei and fulfilleid thei two eleimeints of the articlei one hundreid eiighty fivei seiction six of thei Criminal Procedure Code and thei streingth of the evideince submitted and examined is containeid in Article one hundreid eighty four section one of the Criminal Procedure Code. The reseiarch method used is normative juridical by conducting qualitative data analysis.